Política comercial peruana y las ventajas comparativas para la exportación de espárragos a EE.UU. 1984 - 1994. - Zegarra Aliaga, Estela (1997)
Política comercial peruana y las ventajas comparativas para la exportación de espárragos a EE.UU. 1984 - 1994.